PEMANFAATAN TEKNOLOGI INFORMASI DALAM PENINGKATAN PELAYANAN PEMBUATAN PASPOR BARU DI WILAYAH DKI JAKARTA (Jurnal Pilar Nusa Mandiri, 2013)
Passport is an important document for every Indonesian citizen who will be traveling between countries, but in the process to obtain a passport is a lot of red tape tripping obstacles and complex, so a little more inhibited in the management of passport. The government through the Directorate General of Immigration under the Ministry of Law and the Human Rights Republic of Indonesia made a breakthrough policy is helpful in the management process passports for citizens of Indonesia for easy, fast and effective through the use of information technology. Where present, if an Indonesian citizen wanted for a passport, can pre-register first via the website http://www.imigrasi.go.id. In this study all described in the management information related to passport online to the public, especially residents of Jakarta starting from the data entry applicants to pre-petition receipt printing that can be used as evidence that the applicant is the data contained in the proof of the pre-petition has included documents document requirements in the new passport, so that the applicant can directly execute the process of verifying the authenticity of the document, the process of taking fingerprints and photographs and interview process. This will greatly assist in the management of passport applicants who previously had to take at least up to 8 working days to more easily, quickly and effectively, because if you do the prepetition management of passport takes only 4 working days. So it is clear that the presence of all information technology activities will be faster and more effectively.